2022
DOI: 10.1108/jpbm-05-2021-3470
|View full text |Cite
|
Sign up to set email alerts
|

Is it better to communicate product information abstractly or concretely? The role of consumer product expertise and shopping-stage mindset

Abstract: Purpose This paper aims to investigate the effect of product-related description abstractness/concreteness on perceived trustworthiness and the role of consumer product expertise and shopping-stage mindset in the persuasiveness of abstract vs concrete product descriptions. Design/methodology/approach Two online experiments were conducted: Study 1 (description abstractness – manipulated between-subject; consumer product expertise, perceived trustworthiness, purchase intent – measured), Study 2 (consumer shopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…At the same time, cues that allow consumers to assess the level of trustworthiness, expertise, experience and confidence of a reviewer can represent social heuristics used for decision-making (Ahmad and Guzmán, 2020; Chen et al , 2020; Trzebinski et al , 2022). Consumers can focus in this manner on both the utilitarian and symbolic brand value and precursors of functional and emotional brand relationships (Fernandes and Moreira, 2019; Fetscherin et al , 2021; Yousaf et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, cues that allow consumers to assess the level of trustworthiness, expertise, experience and confidence of a reviewer can represent social heuristics used for decision-making (Ahmad and Guzmán, 2020; Chen et al , 2020; Trzebinski et al , 2022). Consumers can focus in this manner on both the utilitarian and symbolic brand value and precursors of functional and emotional brand relationships (Fernandes and Moreira, 2019; Fetscherin et al , 2021; Yousaf et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of deceptive practices in online consumer reviews, authenticity and how it affects consumer perceptions of reviews is an essential factor for consideration (Chakraborty, 2019). Authenticity is real and genuine, and in the context of luxury brands, it influences image, identity, competitiveness and trust (Stiehler and Tinson, 2015; Trzebinski et al , 2022). Authenticity evaluation is based on several aspects, including individual subjective factors, heuristics, indexical and iconic cues and experiential aspects (Ewing et al , 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, front of packaging is a strategic marketing tool (Chen, 2021;Ku and Chen, 2023;Rundh, 2016), situated at the critical purchasepoint where decisions are made (Jin et al, 2019). As a strategic communicator, food packaging research has examined numerous concepts, including the abstractness of product descriptions (Trzebinski et al, 2023), health attributes through nutrition labelling (Giannattasio et al, 2024;Ku and Chang, 2021) and product attributes (Ku and Chen, 2023). Yet, analysis of front-of-packaging design from a strategic brand management perspective is lacking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the food context, pertinent extrinsic cues pertain to branding, including mascots. Brand names enable consumers to identify quality differences and motivate social recognition (Woo and Kim, 2022), whilst brand slogans impact decision-making (Rybaczewska et al, 2020) and product descriptions are found to influence perceptions of trustworthiness and persuasiveness (Trzebinski et al, 2023). Brand mascots are a defining front-of-packaging cue used in many food categories (i.e.…”
Section: Cue Type: Intrinsic and Extrinsic Cuesmentioning
confidence: 99%
See 1 more Smart Citation